DEVELOPMENT OF THE INFLUENCE OF COLLABORATIVE LEARNING MODELS AND INTERPERSONAL INTELLIGENCE ON STUDENT LEARNING OUTCOMES OF CLASS V SD MUHAMMADIYAH 12 SEI KAMBING - Muda Genali Sakti; Deny Setiawan; Daulat Saragih (Sensei International Journal of Education and Linguistic, 2021)
One alternative to improve and improve learning outcomes is to apply a collaborative learning model, namely a learning model carried out in groups aimed at encouraging students to find various opinions or thoughts issued by each student in the group, not to unite opinions. This study aims to analyze: (1) the effect of the collaborative learning model compared to the conventional learning model; (2) civics learning outcomes of students who have high Interpersonal Intelligence compared to students who have low learning Interpersonal Intelligence (3) the interaction between collaborative learning models and students Interpersonal Intelligence in influencing student civics learning outcomes. The research was in the form of a Quasi-Experimental Design with a 2x2 factorial. The instruments used were the PPKn learning outcomes test and the Learning Interpersonal Intelligence instrument. Data analysis used two-way ANOVA. The results showed: (1) There is an effect of the collaborative learning model on student PPKn learning outcomes in class V SD Muhammadiyah 12 Sei Goat; (2) The learning outcomes of students who have high learning Interpersonal Intelligence are higher than students who have low learning Interpersonal R Intelligence; (3) There is an interaction between the Collaborative learning model and learning Interpersonal Intelligence on the learning outcomes of Student PPKn at SD Negeri Muhammadiyah 12 Sei Kambing.